Impact of Uruguay Round and NAFTA on Commonwealth Caribbean countries with special reference to Jamaica : interim report - Davenport, Michael (Commonwealth Secretariat LondonGB, 1994)
Considers the market access effects in goods and services as well as the trade implications of the Uruguay Round and NAFTA. Looks at the trade preferences and policies of the Commonwealth countries of the Caribbean including the generalized system of preferences; the Lome Convention; Caribbean Basin Initiative; CARIBCAN; CARICOM and other regional trading arrangement policies.